The Influence of Service Quality and Information Quality on the Jamsostek Mobile “JMO” Application Towards Reputational Risk Mediated by Participant Satisfaction - Dwitama, Sony; Buchory, Herry Achmad (Universitas Padjadjaran, 2026)
Digital transformation, exemplified by the BPJS Ketenagakerjaan's Jamsostek Mobile “JMO” application, is a key strategy for improving public services, though it introduces reputational risks. This study examined the impact of service and information quality on reputational risk, with participant satisfaction as a mediating variable. Data were collected from 280 active Jamsostek Mobile “JMO” application users in Greater Bandung (Bandung City, Bandung Regency, West Bandung Regency, and Cimahi City) via purposive sampling and a quantitative survey. The data was analyzed using Structural Equation Modeling (SEM). The results of the study demonstrate that the quality of information and services has a positive and significant impact on participant satisfaction. Furthermore, contentment has a substantial and adverse effect on reputational risk. Additionally, the quality of information and services has a substantial and adverse effect on reputational risk. These findings emphasize the importance of strengthening the functional and informative quality of digital applications as a proactive strategy to build user satisfaction and maintain the institution's reputation. Therefore, strategically managing application quality is crucial in maintaining public trust in digital social service institutions such as BPJS Ketenagakerjaan.